The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.34172/bi.2021.23337
|View full text |Cite
|
Sign up to set email alerts
|

High efficacy of tamoxifen-loaded L-lysine coated magnetic iron oxide nanoparticles in cell cycle arrest and anti-cancer activity for breast cancer therapy

Abstract: Introduction: Due to the side effects of drugs, the development of nanoscale drug delivery systems has led to a significant improvement in medicinal therapies due to drug pharmacokinetics changes, decreased toxicity, and increased half-life of the drug. This study aimed to synthesize tamoxifen (TMX)-loaded L-lysine coated magnetic iron oxide nanoparticles as a nano-carrier to investigate its cytotoxic effects and anti-cancer properties against MCF-7 cancer cells. Methods: Magnetic Fe3O4 nanoparticles were syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 78 publications
1
6
0
Order By: Relevance
“…The developed HMNP efficiently controlled the release of TMX under different release conditions (Figures 6A,B), acting as a promising nanocarrier for cancer nanomedicine. Consistent with the presented results, efficient control over TMX release has been previously reported for other HMNP based on Fe 3 O 4 nanoparticles coated with L-lysine and loaded with this drug (Rostami et al, 2021), thus confirming the potential use of Fe 3 O 4 -containing nanoplatforms for controlled delivery of anticancer therapeutics. As expected, TMX reference sample was released at a faster rate, independently of the medium and temperature.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The developed HMNP efficiently controlled the release of TMX under different release conditions (Figures 6A,B), acting as a promising nanocarrier for cancer nanomedicine. Consistent with the presented results, efficient control over TMX release has been previously reported for other HMNP based on Fe 3 O 4 nanoparticles coated with L-lysine and loaded with this drug (Rostami et al, 2021), thus confirming the potential use of Fe 3 O 4 -containing nanoplatforms for controlled delivery of anticancer therapeutics. As expected, TMX reference sample was released at a faster rate, independently of the medium and temperature.…”
Section: Discussionsupporting
confidence: 91%
“…Even some Fe 3 O 4 -AA conjugates have been used as nanocarriers in the treatment of cancer (Nosrati et al, 2018b;Nosrati et al, 2018c;Rostami et al, 2021), these functionalizations of MNP did not provide cancer-targeting properties. Therefore, to provide the final drug delivery nanoplatform targeting to cancer cells, HA was incorporated into the surface of Fe 3 O 4 -L-Cys nanoparticles (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was in agreement with a study reported by Rostami et al , where tamoxifen-loaded lysin-coated nanoparticles were found equally significant in controlling cell proliferation, as indicated by cell viability assays. In view of this, it is safe to suggest that TMX-AG-INPs are good candidates for breast cancer control evaluation after further studies …”
Section: Discussionmentioning
confidence: 99%
“…Inorganic nanomaterials are modified so that they meet the requirements for their use in the systemic circulation to develop controlled and targeted therapies using a wide variety of small or large molecules [ 3 ]. Iron oxide nanoparticles, for instance, are widely explored in cancer treatment as drug delivery carriers [ 4 , 5 , 6 ] as well as in hyperthermia treatment [ 7 , 8 ]. Moreover, combining inorganic nanoparticles with stimuli-responsive materials led to a great improvement in cancer treatment by enhancing the drug cellular uptake and cytotoxicity of cancer cells.…”
Section: Introductionmentioning
confidence: 99%